PERPUTARAN EKONOMI UMKM LOKAL PADA FESTIVAL GOLO KOE, LABUAN BAJO - Safitri, Ni Wayan Noviana; Siagian, Reynaldo Angga; Rudiyanto, Roseven; Astawa, I Nengah Dasi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.03.TAHUN.2025DO - 10.24843/EEB.2025.v14.i03.p01, 2025)
This study aims to analyze the characteristics and factors influencing the income of Micro Small Medium Enterprises (MSMEs) participating in the Golo Koe Festival at the Waterfront area, Labuan Bajo. Data were collected through direct observation, the distribution of questionnaires, and semi-structured interviews with the stand owners or managers. A sample of 34 MSMEs was selected using stratified random sampling. Data validity was ensured through source triangulation, as well as validity and reliability tests of the questionnaires. The analytical techniques used included descriptive quantitative analysis and multiple regression with SPSS. The results showed that the majority of MSMEs sold food products, followed by crafts and clothing. The participating MSMEs had varying levels of business experience, with most having operated for several years. The regression results indicated that the factors significantly influencing MSME income were the length of business operation and operational costs, while other variables such as participation frequency and the number of employees did not show a significant effect. MSMEs expressed the need for improvements in facilities, more active product promotion, longer festival duration, and more entertainment to attract visitors. These findings provide insights for festival organizers and stakeholders to enhance the experience and income of MSMEs in future similar events.